Are Dietary Cholesterol Intake and Serum Cholesterol Levels Related to Nonalcoholic Fatty Liver Disease in Obese Children?. (3rd July 2012) - Papandreou, Dimitrios; Karabouta, Zaharoula; Rousso, Israel
Abstract : Background . Nonalcoholic fatty liver disease (NAFLD) in children has been recognized as a major health burden. Serum lipids as well as dietary cholesterol (DC) intake may positively relate to development of NAFLD. The purpose of this study was to investigate anthropometric, biochemical, and dietary intake parameters of obese Greek children with and without NAFLD. Materials and Methods . Eighty-five obese children aged 8–15 (45 boys/40 girls) participated in the study. NAFLD was diagnosed by ultrasonography (US) in all subjects. Liver indexes were measured in all children. A 3-day dietary was recorded for all subjects. Results . 38 out of 85 children (44.7%) were found to have fatty liver. Obese children with increased levels of TC (95% CI: 1.721–3.191), low density lipoprotein (LDL) (95% CI: 1.829–3.058), and increased dietary cholesterol intakes (95% CI: 1.511–2.719) were 2.541, 2.612, and 2.041 times more likely to develop NAFLD compared with the children without NAFLD. Conclusion . The present study showed that TC, LDL, and DC were the strongest risk factors of development of NAFLD. Reducing body weight and dietary cholesterol intakes as well as decreasing serum TC and LDL levels are urgently necessary in order to prevent NAFLD and possible other health implications later in life.